The Role of Hearing Aids use on Reading Ability in Deaf Students - Djoko Rianto, Bambang Udji (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Introduction: Reading is a very complex process, which includes the cognitive process, initialized by visual analysis and letter transformation into vocabulary form, word identification by letter sound mapping, correlating words and interpretation. Deafness causes difficulties in acquiring language information via hearing process thus inhibiting a successful conversation process. Hearing aids can amplify sound information to the auditory organs. Objective: To know the effect of hearing aids on deaf students. Methods: A historical cohort design was done. The reading ability of 35 deaf students with hearing aids who received early education were compared to those without hearing aids. The variables measured included age, age of school enrollment, length of studies, degree of deafness, sex, parental educational level. Results: Regression analysis showed that hearing aids plays a role to significantly increase reading ability statistically (p: 0.006; OR: 10.197; 95% CI: 1.939-53.628) compared to students without hearing aids, besides the length of studies variable (p: 0.002; OR: 38.250: 95% CI: 3.739-391.361). Conclusion: This study concluded that the use of hearing aids significantly play a role to increase reading ability in deaf students who receive early education. Key words: hearing aids - deaf student - reading ability.